Diseño de un sistema de buenas prácticas de producción porcina (bppps) en la granja Jarriporsa - Tabacundo - Bohórquez Galarza, Karla Josefina (2012)
The research presented is an analysis of JARRIPORSA Pig Farm, located in Tabacundo – Ecuador, which is producing pigs for 15 years or so. This has vii become more technical gradually during this time, and now seeks the implementation of BPPP’s (Good Manufacturing Practices Swine) in their facilities, animal handling, an waste management or waste produced in the farm, for improve performance and quality of their products allowing them to be more competitive in the market which today is very demanding. A study of the farm seeking to determine whether or not the correct application of Good Practice of Pig Production, using the rules and regulation given by the Ministry of Agriculture...See attached file